PERENCANAAN JALUR PENGANGKUTAN SAMPAH KOTA BANGKALAN DENGAN MODEL DINAMIS - Mohammad Mirwan; Abdul Ghefurulloh (EnviroUS, 2021)
Several cities in Indonesia still experience problems regarding solid waste, especially Bangkalan City which is one of the districts on Madura Island. In managing its solid waste, Bangkalan City has 1 TPA ​​and 12 waste transport fleets with a waste generation of 270.58 m3 / day in 2019. The related agency of Bangkalan City plans to build a new TPA to overcome the waste problem that continues to increase every year. This study aims to plan a route for transporting waste to the new TPA and projecting the need for ritation and the number of transportation fleets for the next 10 years using a dynamic model with the help of STELLA software. The results showed that in 2029 there is a fleet requirement of 40 units and 18 ritation needs with a total waste generation of 302.76 m3 per day. Alternative route 2 is able to save 42.4 km / day mileage and also save Rp. 76,320, - / day or Rp. 2,289,600, - / month and Rp. 27.475.200, - / year.